Anodization Parameters Influencing the Growth of Titania Nanotubes and Their Photoelectrochemical Response. (26th February 2012) - Lim, Ying-Chin; Zainal, Zulkarnain; Tan, Wee-Tee; Hussein, Mohd Zobir
Abstract : TiO2 nanotubes (TNTs) were fabricated by electrochemical oxidation of Ti foil in a standard two-electrode cell-containing NH4 F. The effects of bath temperature, voltage ramp prior to constant voltage held during anodization and present of complexing agent on the crystalline phase, nanotube growth, and dimensional change of TNT were investigated using XRD and FESEM. The results show that tube length decreases with bath temperature attributed to faster chemical dissolution rate at high temperature. However, nanotubes growth rate was enhanced by ~260% with the addition of EDTA as the complexing agent. Meanwhile, the nanotubes diameter was found to be proportionally dependent on bath temperature but independent of the voltage ramp and addition of EDTA. Photoelectrochemical response under illumination was enhanced by using the calcined TNT and is strongly affected by its dimensional changes. Thus, desired properties of TNT can be obtained by tuning the electrochemical condition for a wide-range application.